Interferon Gamma Induces Changes in Natural Killer (NK) Cell Ligand Expression and Alters NK Cell-Mediated Lysis of Pediatric Cancer Cell Lines - Aquino-López, Arianexys; Senyukov, Vladimir V.; Vlasic, Zlatko; Kleinerman, Eugenie S.; Lee, Dean A. (Frontiers in Immunology, 2017)
Natural Killer (NK) cells have therapeutic potential for cancer due to their capacity for targeting tumor cells without prior sensitization. Our laboratory has developed an NK cell expansion protocol that generates large quantities of NK cells for therapeutic infusion that secret 20 times the amount of IFNγ than resting NK cells. IFNγ can upregulate MHC class I, an inhibitory ligand for NK cells, but can also upregulate Intercellular Adhesion Molecule 1 (ICAM-1) which promotes NK:target cell interaction for an efficient lysis. Due to the opposing effects reported for IFNγ on tumor sensitivity to NK cells we evaluated a panel 22 tumor cell lines from the Pediatric Preclinical Testing Program (PPTP) corresponding to different tumor types. We determined the impact of IFNγ on their expression of NK cell activating and inhibitory ligands, death receptors, and adhesion molecules using mass cytometry. We also evaluated the effect of IFNγ on their sensitivity to NK cell mediated lysis. Our results show upregulation of PD-L1, ICAM-1, MHC-class I, HLA-DR, CD95/FasR and CD270/HVEM after IFNγ treatment, this upregulation is variable across different tumor types. We also observed a variable impact of IFNγ in NK cell mediated lysis. For 6 of the cancer cell lines IFNγ resulted in increased resistance to NK cells, while for 3 of them it resulted in increased sensitivity. Modeling of the data suggests that the effect of IFNγ on NK cell-mediated tumor lysis is mostly dependent on changes in MHC-class I and ICAM-1 expression. For 3 of the cell lines with increased resistance we observed higher upregulation of MHC-class I than ICAM-1. For the cell lines with increased sensitivity after IFNγ treatment we observed upregulation of ICAM-1 exceeding MHC-class I upregulation. ICAM-1 upregulation resulted in increased conjugate formation between the NK cells and tumor cells, which can contribute to the increased sensitivity observed. However, the effects of MHC-class I and ICAM-1 are not readily predictable. Due to the high IFNγ secretion of NK cell infusion products a better understanding of the NK ligands on tumor cells and how they are affected by IFNγ is essential to optimize NK cell immunotherapy.